Dark carbon fixation is a common process in the water column of stratified boreal lakes - Martin, Gaëtan; Rissanen, Antti J.; Garcia, Sarahi L.; Peura, Sari (Elsevier, 2025)
CO2 fixation (i.e. primary production) is a key function of all ecosystems, providing the carbon and energy that fuel the entire food web. It also plays an important role in mitigating climate change as CO2 is the most important greenhouse gas. While photosynthesis is regarded as the most important carbon fixation pathway, prokaryotes able to fix carbon in the absence of light (chemolithoautotrophs) can also be a significant source of energy in a light-limited ecosystem. Boreal lakes, notoriously colored and stratified with respect to oxygen and nutrients, present ideal conditions for this so-called dark carbon fixation by the chemolithoautotrophs. However, the prevalence of dark carbon fixation in boreal lakes remains unknown. Here, we measured dark carbon fixation in Swedish lakes from the boreal and boreo-nemoral zones, during summer stratification. We detected dark carbon fixation in 16 out of the 17 lakes studied, and concluded that dark fixation is a widespread phenomenon in boreal lakes. Moreover, the average dark primary production ranged from 18.5 % in the epilimnion to 81.4 % in the hypolimnion of all tested lakes. Our data further suggests that chemolithoautotrophic activity is mostly driven by iron-oxidizing bacteria. The chemolithoautotrophic guild is diverse and seems to be composed of both ubiquitous bacteria, like Gallionellaceae or Chromatiaceae, and endemic taxa, such as Ferrovaceae, which appears to be favored by a low pH. These results are particularly exciting as they suggest that dark carbon fixation could partly compensate for the low photosynthetic capacity in lakes with dark-colored water.
Keywords: dark carbon fixation; boreal lakes; iron cycle; boreal lakes